The outcomes of entrepreneurship, relational capital and innovativeness on tourist satisfaction - Lopes, S.; Dias, Á.; Pereira, L.; Santos, V. (Sustainability, 2022)
Addressing the needs of customers is fundamental to the success of companies, particularly in the long-term. In fact, most companies use customer satisfaction as a method to determine and evaluate their performance and outline their strategies for the future. Therefore, the main objective is to better understand entrepreneurship and new product development antecedents and implications on customer satisfaction, a key element for sustainable development. A model is proposed to assess the relationship between two antecedents of entrepreneurial orientation (EO) and new product development (NPD) and a measure of performance. Based on a survey sample of 137 tourism SMEs, the model was tested using Partial Least Squares (PLS). The results show that both the relational capital and innovativeness positively influence entrepreneurship and NPD. They also suggest a positive relationship between entrepreneurship and customer satisfaction. Although there is a positive impact of NPD on customer satisfaction, this relationship was not significant. In addition, the results indicate that relational capital and innovativeness positively influence customer satisfaction through entrepreneurship and NPD. Consequently, to improve the sustainable performance of tourism firms and to increase customer satisfaction, managers must invest in the development of entrepreneurship as well as in the development of new products and their antecedents.